The Effect of Cerebral Vascular Disease on Skeletal Muscle - Clarke, Beverley (My University, 1986)
Twenty-five patients with a mean age of 59.7 ± 11.8 (SD) years who were hemiparetic due to a cerebrovascular lesion of the cortex were assessed to determine the degree of neuromuscular dysfunction produced in the affected lower limb. Dysfunction was postulated to be the result of a secondary lower motoneuron lesion precipitated by the primary upper motoneuron lesion. The effects of cerebrovascular disease on skeletal muscle were assessed through an evaluation of the motor unit which involved assessment of excitable muscle mass (M-wave amplitudes), motor unit counts, peripheral nerve conduction velocities, evoked contractile properties of the dorsiflexor muscles (tibialis anterior) of the lower limb and degree of motor dysfunction expressed as a function of motor unit activation and maximum voluntary contraction (twitch interpolation method). Results showed preservation of the skeletal muscle with normal contraction times (108 ± 33 ms and 106 ± 35 ms, affected limb versus unaffected limb) and half relaxation times (119.3 ± 41 ms and 114 ± 32 ms respectively). Twitch torque was maintained and did not show significant differences between limbs (2.3 ± 1.6 N.m and 2.4 + 1.5 N.m., paretic vs. non-paretic limb). Voluntary force production of the affected limb, (10 ± 12.1 N.m) however, was 38% of that produced by the unaffected limb (26 + 1.4 N.m.) and measures of mean percent motor unit activation of the paretic limb were 58% of that produced by the unaffected limb. Interpolated twitch results showed that mean percent motor unit activation was significantly different in the affected limb (46 ± 36%) than the unaffected limb (79 + 19.6%). These results indicate that some motoneurone in hemiplegic patients were healthy but not readily activated. No effect was seen for age, sex of the subject and time post stroke. No significant difference in the pattern of results was observed between initial and final test results for subjects examined more than once. Conclusions were that skeletal muscle integrity was preserved probably due to spinal reflex activity and force production was depressed due, in part, to an inability to fully activate motor units. The inability to activate motoneurone may occur because some motoneurone are in a dysfunctional state. The following data from the present experimental work revealed several trends suggesting the possibility of a sick motoneuron hypothesis due to transynaptic motoneuron degeneration and the existence of a secondary lower motoneuron lesion in stroke syndrome. These trends are: 1) decreased motor unit counts of a sub-group of the total sample consisting of subjects under 60 years of age approached conventional levels of significance. Mean values for the affected limb were 73.8 ± 52 and 130.0 ± 61 for the unaffected limb (P < 0.05, F =5.05, critical F =5.59) In addition, M-wave amplitudes showed significant differences between limbs in the sub-group (4.0 + 2.3 mV and 5.7 ± 2.2 mV affected vs unaffected limb p<0.05), indicating that transynaptic motoneuron loss may have occurred; 2) decreased nerve conduction velocities and prolonged terminal latencies in the motor nerves of the paretic limbs also suggest sick motoneurone and the possibility of a dying back phenomenon of the terminal nerve endings; 4) normal M-wave amplitudes and twitch torque values of the tibialis anterior muscle coupled with the prolonged terminal latencies may be indicative of collateral sprouting of terminal axons which have taken over previously denervated muscle fibres. Future studies are needed to confirm or refute these observations.
Keywords: cerebrovascular disease; skeletal muscle